An analysis of the suitability of prescribed geography textbooks for Ciskei pupils in standard 6 - Rulashe, Turbner Mnyamezeli (Rhodes University, Faculty of Education, Department of Education, 1995)
Research has shown that in the South African school context textbooks are perceived as the most important guide to subject content. It is essential, therefore, that pupils and teachers should possess skills and strategies that they can use to interpret and understand the textbook. Equally, textbook writers ought to be aware of the cues pupils need to facilitate the learning process. Problems that hinder the learning of geography subject content from textbooks may arise from, among other things, the style in which the text is written, the way in which concepts are developed, the presentation of visual materials and elements of bias and stereotyping. This study scrutinises and analyses two standard 6 geography textbooks prescribed for Ciskei schools to assess the extent to which these textbooks consider the language competence of the pupils, explain and develop concepts, and in general promote the geographical education. Interviews with Ciskei teachers revealed that Standard 6 pupils encounter difficulties in the geography textbooks which are attributed to the fact that they are second language learners and they lack the requisite skills for interpreting visual materials. The analysis of the textbooks revealed that despite efforts made in recent years to rectify the most blatant aspects of bias and stereotyping and to improve the presentation of textbooks, a number of serious problems continue to exist particularly with regard to the Standard 6 learner of geography. The study attempts to alert writers of texbooks and teachers to factors which need to be taken into consideration to assist second language speakers toward effective learning.
Keywords: Geography -- Study and teaching (Secondary) -- South Africa -- Eastern Cape -- Textbooks -- Evaluation